Influence of paste coating thickness on the compressive strength, permeability, and mesostructure of permeable concrete. (13th September 2021) - Wang, Zhongzhen; Zou, Dujian; Liu, Tiejun; Zhou, Ao
Graphical abstract: Highlights: Influence of PCT and additives on the compressive strength and permeability was investigated. Low strength ratios of permeable concrete to cement paste results from the low bonding area. Enhanced bonding ratio can produce the greatest benefit in terms of strength. Loss of permeability is the result of both reduced connected porosity and increased tortuosity. Cement paste thickness distribution and pore size distribution were predicted by lognormal function. Abstract: The macro performance and mesostructure of permeable concrete are largely determined by the paste coating thickness (PCT) on aggregates within the fresh mixture. Accordingly, in the present study, the strength and permeability of permeable concrete with different paste coating thicknesses were measured. The mesostructure characteristics of cement paste and pore were subsequently quantified by X-ray CT images and image processing techniques. As a result, the influence of PCT on the compressive strength and permeability, the characteristics of cement paste and pore was determined. The distribution of cement paste thickness and total pore size were used as functions of paste coating thickness, which coud be used to predict these mesostructure characteristics at the design stage of permeable concrete. The significance of this paper includes providing a deeper understanding of the relationship between macro performance and mesostructure from the perspective of paste coating thickness within mixtures.